The formation of young athletes' specialization on the example of rhythmic gymnastics group exercises - Syvash, I. S. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2014)
Purpose: to substantiate the approach to the formation of specializations gymnasts in the initial stages and preliminary basic training. On this basis, to develop the technology selection, orientation and training of athletes in rhythmic gymnastics group exercises.